The polymorphic CAG repeat in exon 1 of androgen receptor is associated with level of HDL cholesterol and hypertension in Chinese middle‐aged and elderly men. (6th April 2017) - Yang, Deyu; Tian, Jinhai; Zhang, Xu; Yu, Jingjing; Li, Shuya; Wang, Zhizhong; Ma, Yuying; Liu, Lan; Huang, Qi; Ma, Rong; Wang, Jia; Li, Xin; et al.
Summary: Objective: The length of the CAG repeats in exon 1 of the androgen receptor ( AR ) gene has been shown to be inversely correlated with AR transcriptional activity. This study aimed to investigate the correlations between the length of CAG repeat in AR and serum lipids and hypertension in Chinese men. Design and patients: The relationship between length of the CAG repeat in exon 1 of AR with prevalence of hypertension and the levels of serum lipids among Chinese men (aged ≥40 years). Measurements: The physical condition of the subjects was examined and recorded. The concentrations of blood lipids and sex hormones were measured, and the CAG repeat lengths of the AR gene were determined. Results: The length of the AR CAG repeats was associated with HDL cholesterol (HDL‐C) concentration, and the stepwise multiple regression model showed that this association was independent of body mass index (BMI), triglycerides (TG) and total cholesterol (TC), although these factors influence HDL‐C concentration. Furthermore, men with <22 vs men with ≥22 CAG repeats showed higher blood pressure and higher prevalence of hypertension. Shorter CAG repeat numbers were associated with the increased risk of hypertension in a multivariate logistic regression analysis (odds ratio = 0·715; 95% confidence interval, 0·517–0·989; P  = 0·043). No significant correlation of AR CAG repeat polymorphism with sex hormone levels, TG, LDL cholesterol (LDL‐C) or TC was found. Conclusions: This study provides evidence that men carrying shorter (<22) AR CAG repeats have lower HDL‐C level and increased risk of hypertension. The androgenic activity may differ due to the polymorphic length of CAG repeats of the AR gene.